2019
DOI: 10.1017/jog.2019.6
|View full text |Cite
|
Sign up to set email alerts
|

Ice flow variations at Polar Record Glacier, East Antarctica

Abstract: Relatively little is known about the physical mechanisms that drive the dynamics of the East Antarctic outlet glaciers. Here we conduct a remote-sensing investigation of the Polar Record Glacier (PRG), East Antarctica to analyze its ice flow acceleration, ice front variations and ice surface melting. Ice flow speeds at PRG increased by up to 15% from 2005 to 2015, with substantial interannual fluctuations. The ice velocities also showed seasonal variations, accelerating by up to 9% between September and Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Recent work from Greenland has demonstrated a clear correlation between total lake area and annual surface runoff 21 , as well as their inland expansion during more intense melt years and over decadal time-scales 7,22,24 . Localised studies in East Antarctic have found similar relationships 31,53 . Thus, any future warming in East Antarctica is likely to lead to similar increases in the cumulative area of SGLs and the locally-enhanced melt associated with their development is likely to play a greater role in the surface mass balance 20 .…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Recent work from Greenland has demonstrated a clear correlation between total lake area and annual surface runoff 21 , as well as their inland expansion during more intense melt years and over decadal time-scales 7,22,24 . Localised studies in East Antarctic have found similar relationships 31,53 . Thus, any future warming in East Antarctica is likely to lead to similar increases in the cumulative area of SGLs and the locally-enhanced melt associated with their development is likely to play a greater role in the surface mass balance 20 .…”
Section: Discussionmentioning
confidence: 69%
“…It has been noted, however, that percolation and refreezing of meltwater into the firn layer can exert a localised warming effect on ice temperatures through the release of latent heat 51,52 . Indeed, recent work on one outlet glacier in East Antarctica has hypothesized that englacial penetration of meltwater and/or the filling of crevasses can increase the ice temperature, soften the ice, and lead to a seasonal speed-up of ice shelf flow 53 . Moreover, future warming is likely to increase surface melting in Antarctica 4,20,29,34,54,55 .…”
Section: Discussionmentioning
confidence: 99%
“…Ice surface depressions on grounded ice are translations of subglacial topographic undulations and are therefore fixed in space rather than migrating with ice flow (Echelmeyer et al, 1991;Lampkin and VanderBerg, 2011;Langley et al, 2016). Conversely, lakes on the ice shelf itself are generally shorterlived because they form in surface depressions that migrate annually with ice flow and are progressively advected towards the ice shelf front, as on other Antarctic ice shelves (Banwell et al, 2014;Bell et al, 2017;Glasser and Gudmundsson, 2012;Luckman et al, 2014;Reynolds and Smith, 1981). We speculate that surface undulations perpendicular to the grounding line (i.e.…”
Section: Spatial Distribution Of Sglsmentioning
confidence: 94%
“…However, few studies have conducted detailed analyses of the seasonal behaviour and spatial distribution of SGLs on ice shelves in East Antarctica. As such, direct observations of lake interactions and drainage are currently constrained to a limited number of ice shelves Bell et al, 2017;Langley et al, 2016;Liang et al, 2019;Moussavi et al, 2020;Kingslake et al, 2015), and our understanding of the importance of SGL evolution on ice shelf instability remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…As such, direct observations of lake interactions and drainage are currently constrained to a limited number of ice shelves (Banwell et al, 2019;Bell et al, 2017;Langley et al, 2016;Liang et al, 2019;Moussavi et al, 2020;Kingslake et al, 2015), and our understanding of the importance of SGL evolution on ice-shelf-instability remains limited.…”
mentioning
confidence: 99%